2021
DOI: 10.1177/11786329211019225
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices Regarding COVID-19 prevention among Vietnamese Healthcare Workers in 2020

Abstract: Introduction: Healthcare workers (HCWs) are at the frontline of COVID-19 control and prevention but also are high-risk groups for COVID-19 infection. The low level of knowledge and negative attitudes toward COVID-19 among HCWs can lead to inappropriate responding, wrong diagnoses, and poor practices for prevention. This research aims to examine the knowledge, attitudes, and practices regarding COVID-19 prevention and factors influencing the practices among HCWs in Daklak province, Vietnam. Method: A cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
6
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 11 publications
4
32
6
5
Order By: Relevance
“…On the other hand, the results of our study on the good knowledge of communicable diseases were better than some studies were conducted in the Western Development Region, Nepal (32), and other regional hospitals in Trinidad and Tobago (33), and also a study in Palestine Governmental Hospital (13) found (28%, 20%, and 18%, respectively). We also mention that in other studies, a high level of knowledge was found among health workers in Dessie Referral Hospital, South Wollo (34), and also in Vietnam (35) it was found (95.7% and 91.3%, respectively).…”
Section: Knowledge Of Health Workers Regarding Communicable Diseases ...supporting
confidence: 64%
“…On the other hand, the results of our study on the good knowledge of communicable diseases were better than some studies were conducted in the Western Development Region, Nepal (32), and other regional hospitals in Trinidad and Tobago (33), and also a study in Palestine Governmental Hospital (13) found (28%, 20%, and 18%, respectively). We also mention that in other studies, a high level of knowledge was found among health workers in Dessie Referral Hospital, South Wollo (34), and also in Vietnam (35) it was found (95.7% and 91.3%, respectively).…”
Section: Knowledge Of Health Workers Regarding Communicable Diseases ...supporting
confidence: 64%
“…In other words, personal attitude may be crucial for prevention practice in COVID-19 infection. These findings may be different from a study from Vietnam which reported that knowledge was a significant factor associated with practice level (p 0.00) but not barriers of practice ( p 0.056) [ 12 ]. It might be due to differences on questions in the questionnaire.…”
Section: Discussioncontrasting
confidence: 97%
“…Also, there were few cases of COVID-19-infected children reported in Thailand during the study period, Subsequently, the low score on the question about children resulting in negative association with the preventive behavior. Other possible explanations are the shortage of personal protective equipments at that period of time for whole country and finally HCWs may feel difficult to change their habits as previously reported [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Education with a higher level answers knowledge items better so that they have positive attitudes and practices towards COVID-19 prevention 23,27,30 . This is also found in this study.…”
Section: Discussionmentioning
confidence: 99%